Calculation of the electronic, nuclear, rotational, and vibrational stopping cross sections for H atoms irradiation on H2, N2 and O2 gas targets at low collision energies - Cabrera-Trujillo, Remigio; El Hachimi, Abdel Ghafour (Journal of physics. B, Atomic, molecular and optical physics, 2020)
In this work, we present a study of hydrogen atoms interacting with hydrogen, nitrogen, and oxygen molecules in the gas phase in order to determine the projectile energy loss, the stopping cross section, and energy deposition with implication in hydrogen and proton dosimetry and radiotherapy. Our calculations are performed with a density-functional tight-binding (DFTB) as well as by an ab initio electron-nuclear dynamic (END). The H atoms have a low collision energy in the range of 1-100 eV for the DFTB and 1-1000 eV for the END. We decompose the projectile energy deposition into its electronic, nuclear, rotational, and vibrational energy target contributions. We find that for low collisions energy, DFTB and END are in fair agreement when comparing the nuclear and rotational contributions. However, we find discrepancies for the vibrational and electronic energy loss between both approaches. The largest discrepancy is found in the electronic energy loss as DFTB carries the electronic dynamics in the ground state. We confirm that the electronic stopping cross section is proportional to the projectile velocity as obtained by END showing a threshold effect and that it is underestimated by codes like SRIM. Our study shows that at low collision energies a quantum-classical molecular dynamics approach as DFTB can be used to determine the energy-loss process of a projectile penetrating a material target. Finally, we compare our results to available experimental data finding good agreement when extrapolated to high collision energies.